Hubungan Supervisi Kepala Ruangan Dengan Kepatuhan Tenaga Kesehatan Dalam Menjalankan Standar Operasional Prosedur Pemasangan Infus Di UPTD Puskesmas Mawasangka TimurTahun 2023 - Irfan Purnawan; Sancka Stella G. Sihura (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Infusion is one of the invasive procedures performed by health workers by injecting a certain amount of fluid into the body into the vein to improve or prevent fluid and electrolyte, blood, and nutritional disturbances. The act of installing an infusion will be of high quality if in its implementation it always complies with the standards that have been set. One of the factors that can affect the performance of nurses, including the compliance of nurses and midwives in providing actions according to the SOP is supervision. This study aims to analyze the relationship between the supervision of the head of the room and the compliance of health workers in carrying out standard operating procedures for infusion at the UPTD Puskesmas Mawasangka Timur in 2023. This study is a correlation analytic study with a cross sectional study design. The sample in this study was 41 people consisting of 21 nurses and 20 midwives. The sampling technique used in this study is nonprobability sampling with total sampling. Data were analyzed using the chi-square test to determine the relationship between the independent and dependent variables. The results of statistical tests showed that there was a relationship between the supervision of the head of the room and the compliance of health workers in carrying out standard operating procedures for infusion at the Mawasangka Timur Health Center UPTD in 2023 (p-value 0.000 <0.05). Supervision of the head of the room has a significant role in increasing the compliance of health workers, especially nurses and midwives, in carrying out standard operational procedures for infusion installation.